(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Krimidanta (Dental caries) is a common disease in Sri Lankan society. Preschool and schoolchildren are mostly affected by this condition. It is mostly affected on due to very low socioeconomic backgrounds with highly caryogenic dietary patterns, poor brushing habits and low value placed on oral health. Ayurveda authentic classic mentions this condition under the Mukha Roga of Shalakya tantra. According to main authentic classics of Ayurveda, such as Susruta samhita, Astanga Hradaya samhita and Bhavaprakasha clearly mention the condition of Krimidanta and its treatment procedure. A literature study was carried out to collect and analyze the formulas mentioned in well-known traditional texts including Sarartha samgraha, Bhaisajja Manjusa, Prayogaratnavali, Yogarnava, Varayogasara and 21 books of Thalpathe piliyam in indigenous medicine in Sri Lanka. According to the findings, 92 individual herbals materials (Udbhida Dravya), 7 Animal materials (Jangama Dravya) and 5 Minerals (Parthiva Dravya) have been used to treat Krimidanta. Among them mostly mentioned herbs are Welkahambiliya (Tragia hispida), Wara (Calotropis gigantea), Attana (Datura metal), Inguru (Zingiber officinale), Tibbatu (Solanum torvum), Aralu (Terminalia chebula), Walagasal (Embelia ribes) and Diya beraliya (Monachoria hastata. And also Heen bovitiya (Osbeckia octandra), Heen udupiyaliya (Desmodium triflorum), Kebella (Aporusa lindleyana), Kiriwalla (Holarrhena mitis) and Niyada (Sansevieria zeylanica) are found as endemic herbs in Sri Lanka. In the management of Krimidanta, Karna Dhupana, Karna Purana, Dhuma, Kawala external paste application for relevant cheek and Kemkrama were identified as exclusive treatment procedures in indigenous medicine. It was concluded that more herbal, several animal and mineral materials have been used for Krimidanta with exclusive treatment procedures in indigenous medicine in Sri Lanka.